Toward Literature and Language Teaching: Uncovering the Potential of Drama for English Learning - Budiman, Jeihn N. C.; Ganap, Nindy N. (English Education Postgraduate Program, Universitas Negeri Manado, 2024)
This study explores the uncharted territory of integrating drama into literature and language teaching, aiming to unveil its untapped potential for English language learning. Titled